Inability of GSTT1 to activate iodinated halomethanes to mutagens in Salmonella. (15th February 2021) - DeMarini, David M.; Warren, Sarah H.; Smith, Weston J.; Richardson, Susan D.; Liberatore, Hannah K.
Abstract: Drinking water disinfection by‐products (DBPs), including the ubiquitous trihalomethanes (THMs), are formed during the treatment of water with disinfectants (e.g., chlorine, chloramines) to produce and distribute potable water. Brominated THMs (Br‐THMs) are activated to mutagens via glutathione S ‐transferase theta 1 (GSTT1); however, iodinated THMs (I‐THMs) have never been evaluated for activation by GSTT1. Among the I‐THMs, only triiodomethane (iodoform) has been tested previously for mutagenicity in Salmonella and was positive (in the absence of GSTT1) in three strains (TA98, TA100, and BA13), all of which have error‐prone DNA repair (pKM101). We evaluated five I‐THMs (chlorodiiodomethane, dichloroiodomethane, dibromoiodomethane, bromochloroiodomethane, and triiodomethane) for mutagenicity in Salmonella strain RSJ100, which expresses GSTT1, and its homologue TPT100, which does not; neither strain has pKM101. We also evaluated chlorodiiodo‐, dichloroiodo‐, and dibromoiodo‐methanes in strain TA100 +/− rat liver S9 mix; TA100 has pKM101. None was mutagenic in any of the strains. The I‐THMs were generally more cytotoxic than their brominated and chlorinated analogues but less cytotoxic than analogous trihalonitromethanes tested previously. All five I‐THMs showed similar thresholds for cytotoxicity at 2.5 μmoles/plate, possibly due to release of iodine, a well‐known antimicrobial. Although none of these I‐THMs was activated by GSTT1, iodoform appears to be the only I‐THM that is mutagenic in Salmonella, only in strains deficient in nucleotide excision repair ( uvrB ) and having pKM101. Given that only iodoform is mutagenic among the I‐THMs and is generally present at low concentrations in drinking water, the I‐THMs likely play little role in the mutagenicity of drinking water.